MARKET REACTIONS TO THE RUSSIAN INVASION: A STUDY OF LQ-45 AND JII STOCKS - 'Uyuunul Husniyyah; Muhtadin Amri; Yunaita Rahmawati (UIN Sunan Gunung Djati Bandung, 2023)
Investors who consider making an investment consider economic and non-economic market information. Information circulating can send signals that cause market reactions, such as the invasion of Ukraine by Russia. Investors may anticipate receiving bad news from this event. The aim of this research is to determine the impact of the Russian invasion of Ukraine on trading volume activity (TVA), average abnormal returns (AAR), and abnormal returns (AR). The presence of AR on the day of the event, as well as variations in AAR and TVA before and after the event, are indicators of impact. This study uses a quantitative approach. The population of this research is all companies registered in LQ-45 and the Jakarta Islamic Index (JII). An important finding from this research is that shares of companies included in the LQ-45 index have AR on Day 3; The AAR of companies listed in the LQ-45 and JII indices was less affected by the Russian invasion of Ukraine; and TVA shares of companies listed on the LQ-45 and JII indices were significantly impacted by Russia's invasion of Ukraine. The findings of this research indicate that investors must be more careful and vigilant when interacting with non-economic events that may contain information.